A cdc2-like kinase phosphorylates histone H1 in the amitotic macronucleus of Tetrahymena. - Roth, S Y (1991)
Genetic and biochemical studies have shown that cdc2 protein kinase plays a pivotal role in a highly conserved mechanism controlling the entry of cells into mitosis. It is generally believed that one function of cdc2 kinase is to phosphorylate histone H1 which in turn promotes mitotic chromosome condensation. However, direct evidence linking H1 phosphorylation to mitotic chromatin condensation is limited and the exact cellular function(s) of H1 phosphorylation remains unclear. In this study, we show that mammalian cdc2 kinase phosphorylates H1 from the amitotic macronucleus of Tetrahymena with remarkable fidelity. Furthermore, we demonstrate that macronuclei from Tetrahymena contain a growth-associated H1 kinase activity which closely resembles cdc2 kinase from other eukaryotes. Using polyclonal antibodies raised against yeast p34cdc2, we have detected a 36 kd immunoactive polypeptide in macronuclei which binds to Suc1 (p13)-coated beads and closely follows H1 kinase activity. Since macronuclei divide without mitotic chromosome condensation, these data demonstrate that H1 phosphorylation by cdc2 kinase may be necessary, but is not sufficient to promote mitotic chromatin condensation. The fact that an activity which strongly resembles mammalian cdc2 kinase is active during cell growth in a nucleus which does not undergo mitosis and chromosome condensation suggests that other factors are needed for a true mitotic division to occur. These data also reinforce the notion that H1 phosphorylation has important functions outside mitosis both in Tetrahymena and in mammalian cells.